APEC y Perú: estableciendo nuevos vínculos con Asia Pacífico - Ferrero, Alfredo (2000)
Asia-Pacific Economic Cooperation (APEC) was established in 1989 in response to the growing interdependence among Asia-Pacific economies. APEC begun as an informal dialogue group, however, it has become the primary regional vehicle for promoting open trade and practical economic cooperation. lts goal is to advance Asia-Pacific economic dynamism and sense of community. Nowadays, the 21 member economies that form APEC have a combined Gross Domestic Product of over US$18 trillion and 43.85 percent of global trade (1999).